PENGARUH PENERAPAN MEDIA AUDIO VISUAL TERHADAP AKTIVITAS BELAJAR SISWA KELAS VIII DI MTs DARUN NAJAH OGAN ILIR - Ikke Yumelda; Fajri Ismail; Herman Zaini (PAI RAFAH, 2021)
This study aims to determine the increase in learning activities of control class and experimental class students who are applied audio visual compact disc (CD) learning media on the subject of Islamic cultural history class VIII at MTs Darun Najah Ogan Ilir. This type of research is quantitative research with experimental research methods (experimental method) using research design Tru Esperimental design. The data sources consist of primary and secondary data sources. Then the population is 82 students and the sample is 30 students. Data collection techniques are observation, tests, and documentation. Then the data analysis technique used the "t" test. The results of the study were students' learning activities when not applying audio visual media (CD) using the 't' test in class VIII.6 (control), which amounted to 31 students in the moderate category where 26 of the 31 students were included in the medium category or as many as 81.25 % of all students. Student learning activities when implementing audio visual media (CD) learning media using the 't' test in class VIII.7 (experiment), which amounted to 31 students began to increase even though it was still in the moderate category where 30 of the 31 students were included in the medium category or as much as 96.875% of the whole student. the effect of the application of the numbered head together learning model using Audio Visual Media (CD) in increasing student learning activities in the subject of Islamic Cultural History, the material of the establishment of the Abbasid Dynasty class VIII at MTs Darun Najah Ogan Ilir. This can be seen from the results of data calculations using the t test. the result is tcount> ttable (2.66 <6.20> 2.00)